Screening for congenital hypothyroidism in Charikot using cord blood: a single center retrospective study - Dhungana, Rakshya; Neupane, Aashish; Shrestha, Gyanswhor; Pokharel, Anurag (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Congenital hypothyroidism is a major preventable cause of mental retardation in newborns. According to the screening protocol, neonates with abnormal TSH are recalled for confirmatory tests. According to the American Academy of Pediatrics, the appropriate recall rate after primary thyroid stimulating hormone (TSH) screening is approximately 0.05%. The recommended recall rate was 0.05%, but there is around 0.01 to 13% recall rate worldwide. Our study aims to evaluate the value of cord blood TSH for screening rather than the ideal use of TSH at 72 hours after birth. It would be essential to improve our screening programs with cost-feasible and noninvasive. Method: A descriptive retrospective study was done in Charikot Dolkha to analyze the recall rate for a repeat TSH when the cord sample is positive for congenital hypothyroidism. Descriptive analysis was performed with a chi square test for inferential statistics (p 0.05 considered significant). Result: The recall rate or positive screening rate was 1.8%, the positive prevalence rate was 18.2%, and the overall prevalence rate was 0.33%. This result is higher than the American Academy of Pediatrics estimated but within the range of recall rates worldwide. Conclusion: The recall rate is significant, and our study’s prevalence rate is low. A higher cutoff of >30 mIU/L can be considered, but more extensive population-based studies are required to establish a higher normative value.